2014
DOI: 10.3311/pptr.7068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traffic Conflict Characteristic at Temporary Reversible Lane

Abstract: The characteristics of traffic conflicts occurring at the time of direction changes were analyzed to better understand the problems of a temporary reversible lane. Using Huangpu Road as the investigation site, data of traffic conflicts before and after direction changes were investigated. The data on traffic conflict characteristics were compared and analyzed with mathematical statistics. Using the regression analysis method, a prediction model of the traffic conflicts was constructed. This paper also discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Currently, this strategy is applied to median lanes in multilane roads. Up until now, reversible lanes are of complex implementation because of the difficult adjustment for human driving and the need for investment in variable traffic signs [1]. Previous research on road safety has always revealed that reversible lanes have negative impacts on road safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, this strategy is applied to median lanes in multilane roads. Up until now, reversible lanes are of complex implementation because of the difficult adjustment for human driving and the need for investment in variable traffic signs [1]. Previous research on road safety has always revealed that reversible lanes have negative impacts on road safety.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 2000s, the benefits of such a strategy were evident in road capacity increase and were applied in many facility types [12,13]. However, in the human-driven vehicles paradigm, traffic conflicts have been identified due to the human maladaptation to reversible lanes, which leads to low operating efficiency and a low lane utilization rate [1,14]. In practice, reversible lanes are applied as median reversible lanes in bridges [9] and freeway construction zones [15].…”
Section: Introductionmentioning
confidence: 99%
“…al., 2014. The results of the accident reconstructions are useful in developing recommendations for making transport infrastructure and vehicles safer (Cao et. al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other innovative techniques have been presented to affront traffic jams, i.e. temporary use of reversible lanes within the network (Cao et al 2014) or road infrastructure booking (Soltész et al 2011).…”
Section: Introductionmentioning
confidence: 99%